Prognostic role of neutrophil-to-lymphocyte ratio (NLR) in urological tumors: an umbrella review of evidence from systematic reviews and meta-analyses. (3rd June 2021) - Mjaess, Georges; Chebel, Roy; Karam, Aya; Moussa, Ilan; Pretot, Dominique; Abi Tayeh, Georges; Sarkis, Julien; Semaan, Albert; Peltier, Alexandre; Aoun, Fouad; Albisinni, Simone; Roumeguère, Thierry
Abstract: Background: Neutrophil-to-lymphocyte ratio (NLR) has been studied as a biomarker for cancer prognosis, predicting survival in many tumors. The aim of this umbrella review was to combine the results from all systematic reviews and meta-analyses related to the prognostic role of the NLR in patients with urological tumors. Methods: A PubMed, Scopus, Embase and Cochrane search was undergone from inception through September 2020 for systematic reviews and meta-analyses investigating the prognostic value of NLR in urological tumors, subdivided into prostate cancer, renal cell carcinoma, urothelial bladder and upper tract carcinomas PROSPERO (CRD42020216310). Results: The results have shown, with a high level of evidence, that an elevated NLR predicts worse overall survival (OS), progression-free survival (PFS) and relapse-free survival (RFS) in prostate cancer, worse OS, PFS and RFS in renal cell carcinoma, worse OS, PFS, RFS and cancer-specific survival (CSS) in muscle invasive bladder cancer, worse PFS and RFS in non-muscle invasive bladder cancer, and worse OS, PFS, RFS and CSS in urothelial upper tract carcinoma. Conclusion: NLR has a significant prognostic value in urological tumors and should be included in prognostic scores of these cancers.